High-wear-resistance high-chromium cast iron material and heat treatment process thereof

By using iron-coated zirconia toughened alumina ceramics and titanium cubic boron nitride powder in high chromium cast iron materials, combined with heat treatment processes of graded cooling and three-stage tempering, the material is solved in large impact and stress. The fracture problem under the bottom significantly improves its hardness, impact toughness and wear resistance.

CN119464635AActive Publication Date: 2025-02-18SHANDONG SHENGDE MASCH CO LTD

Patent Information

Application Number
CN202411760505.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-18
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

Existing high-chromium cast iron materials are prone to fracture failure under large impact and high stress conditions, and traditional heat treatment processes cannot simultaneously improve their hardness and impact resistance. There is a crack problem caused by the difference in thermal expansion coefficient of ceramic particles.

Method used

Iron-coated zirconia toughened alumina ceramics are used as reinforced phase materials, and the cladding layer is prepared by titanium-coated cubic boron nitride powder, graphite and nickel-based alloy powder. The heat treatment process of graded cooling and three-stage tempering is prepared. High chromium cast iron materials with high hardness, high impact toughness and high wear resistance.

Benefits of technology

It significantly improves the hardness, impact toughness and wear resistance of high-chromium cast iron materials, reduces the internal and external temperature difference and thermal stress during cooling, reduces the risk of cracking, and improves the mechanical properties of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of wear-resistant materials, and discloses a high-wear-resistance high-chromium cast iron material and a heat treatment process thereof, and the heat treatment process comprises the following steps: taking iron-coated zirconium oxide toughened aluminum oxide ceramic as a reinforcing phase material; the casting is placed in a heat treatment furnace, and the casting is cooled to the room temperature in a graded mode after being heated in the furnace; then carrying out three-stage tempering to obtain a machined part; the cut machined part is subjected to surface cleaning and preheating, and a pretreated machined part is obtained; the preparation method comprises the following steps: uniformly mixing titanium-plated cubic boron nitride powder, graphite, nickel-based alloy powder and a binder, pre-placing the mixture on the surface of a pre-treated workpiece, and preparing a cladding layer by utilizing laser cladding to obtain the high-wear-resistance high-chromium cast iron material. And a cladding layer is prepared from titanium-plated cubic boron nitride powder, graphite and nickel-based alloy powder, and the high-chromium cast iron material with high hardness, high impact toughness and high wear resistance is prepared in a graded cooling and three-stage tempering mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wear-resistant materials, and in particular relates to a high-wear-resistant high-chromium cast iron material and a heat treatment process thereof. Background Art

[0002] High chromium cast iron is a widely used wear-resistant material with the advantages of high strength and good wear resistance. It is a white cast iron with a chromium content of 14-30%. The addition of a large amount of chromium makes the organization contain a certain amount of M7C3, M 23 C6 and M3C carbides have high hardness and are the hard phases in high chromium cast iron. They have high wear resistance, especially the microhardness of M7C3 carbides is as high as 1300~1800HV. Chromium can quickly generate Cr2O3 oxide film at high temperature, which helps to prevent and delay oxidation. As an excellent anti-abrasive wear material in contemporary times, high chromium cast iron is widely used in metallurgy, mining, construction, electric power, machinery and other industries.

[0003] The microstructure of ordinary cast high-chromium cast iron contains a large number of sharp chrysanthemum-shaped carbides, which play a role in stress concentration, thereby reducing toughness and easily leading to premature fracture failure, which limits the use of high-chromium cast iron under large impact and high stress conditions. In addition, the heat treatment process of the prior art adopts quenching plus high-temperature tempering or quenching plus low-temperature tempering. Although the wear-resistant material obtained by quenching plus high-temperature tempering has good impact toughness, it has low hardness, poor wear resistance, and is easily deformed by impact. Although the hardness of the wear-resistant material obtained by quenching plus low-temperature tempering is improved, the impact resistance is extremely poor. And with the increasingly harsh service environment, traditional high-chromium cast iron cannot meet the needs of use. The prior art improves its performance by adding ceramic particles. Due to the large difference in the thermal expansion coefficient between the high-chromium cast iron matrix and the ceramic particles, it is easy to cause problems such as cracks and ceramic particles falling off, thereby affecting its mechanical properties. Summary of the invention

[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a high-wear-resistant high-chromium cast iron material and its heat treatment process, using iron-coated zirconia toughened alumina ceramics as the reinforcing phase material, and using titanium-coated cubic boron nitride powder, graphite and nickel-based alloy powder to prepare the cladding layer, and adopting graded cooling and three-stage tempering to prepare a high-chromium cast iron material with high hardness, high impact toughness and high wear resistance.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A heat treatment process for a high-wear-resistant high-chromium cast iron material comprises the following steps: A. Place the casting in a heat treatment furnace, raise the temperature in the furnace to 850~900℃, keep it warm for 5~10min, then heat it to 970~1100℃ at a heating rate of 30~40℃ / min, keep it warm for 20~30min, then cool it to room temperature in stages; B. Use a muffle furnace to temper the quenched casting. The first tempering temperature is 350~400℃, and the temperature is kept for 10~12h. The second tempering temperature is 300~320℃, and the temperature is kept for 12~15h. The third tempering temperature is 280~300℃, and the temperature is kept for 17~20h to obtain the processed parts. C. Cut the workpiece into the required size by wire cutting, grind the surface with a grinder and sandpaper, clean it with alcohol and blow it dry, preheat it at 275-350℃, and obtain the pretreated workpiece; D. Mix titanium-coated cubic boron nitride powder, graphite and nickel-based alloy powder evenly, place them in a drying oven to dry them to remove moisture, and pre-place them on the surface of the pre-treated workpiece with a binder. Then, under the protection of argon gas, use laser cladding to prepare a cladding layer to obtain a high-wear-resistant high-chromium cast iron material.

[0006] Preferably, the specific steps of graded cooling in step A are: first cooling to 940-1070°C and keeping warm for 20-30min, cooling to 710-840°C at a cooling rate of 10-12°C / s after the insulation, cooling to 620-750°C at a cooling rate of 18-22°C / s, then cooling to 500-560°C at a cooling rate of 11-13°C / s, keeping warm for 30-60min, and finally cooling to room temperature at a cooling rate of 280-305°C / min.

[0007] Preferably, the method for preparing the casting in step A comprises the following steps: A1. Weigh the raw materials according to the mass percentage of each alloy element: C: 3.2~3.6%, Cr: 24~27%, Mn: 0.6~1.2%, Cu: 0.4~0.6%, Si≤1.00%, S≤0.06%, P≤0.06%, and the balance is Fe, place them in an induction furnace, heat and raise the temperature until all the raw materials are melted, remove impurities, and obtain molten iron; A2, taking zirconia toughened alumina ceramics and placing them in a quartz boat, covering them with dry anhydrous ferrous chloride, and then placing them at the bottom of a quartz tube, passing argon as a protective gas, and using chemical vapor deposition to deposit an iron coating on the surface of the zirconia toughened alumina ceramics to obtain iron-deposited zirconia toughened alumina ceramics; A3. The iron-deposited zirconia toughened alumina ceramics are embedded in plastic foam, and cast using molten iron by lost foam casting at a temperature of 1600-1780°C to obtain a casting.

[0008] Preferably, the chemical vapor deposition process conditions in step A2 are: deposition temperature 620-700°C, heating rate 3-6°C / min, and hydrogen is introduced after the temperature rises to 620-700°C, with a hydrogen flow rate of 190-210 mL / min.

[0009] Preferably, the preparation method of titanium-coated cubic boron nitride in step D comprises the following steps: placing cubic boron nitride, titanium trichloride and titanium hydride powders into a plating container, setting the plating temperature to 760-795°C, the vacuum degree to 0.01-0.05Pa, keeping warm for 10-20min, maintaining the vacuum degree to 0.01-0.05Pa, cooling to room temperature with the furnace, and preparing titanium-coated cubic boron nitride.

[0010] Preferably, the mass ratio of the cubic boron nitride, titanium trichloride and titanium hydride powder is 97-105:1.5-3:14.5-17.

[0011] Preferably, in step D, the mass ratio of titanium-coated cubic boron nitride powder, graphite and nickel-based alloy powder is 2.7-5.5:1:2.4-3.5.

[0012] Preferably, the nickel-based alloy powder in step D is Ni60 self-fluxing powder, and the mass fractions of the chemical components are 15.5% Cr, 3.5% B, 4.0% Si, 0.8% C, 15.0% Fe, 3.0% W, and the rest is Ni; and the binder is sodium water glass.

[0013] Preferably, the laser cladding process conditions in step D are: laser power 2.2-2.5 kW, laser scanning speed 240-260 mm / min.

[0014] A high-wear-resistant high-chromium cast iron material is obtained by using the heat treatment process as described above.

[0015] Beneficial effects of the present invention: The present invention utilizes chemical vapor deposition to deposit a uniform, continuous and dense iron coating on the surface of zirconium oxide toughened alumina ceramics, and adopts lost foam casting to obtain a casting by using molten iron for casting, which is beneficial to improving the interface bonding performance between high chromium cast iron and zirconium oxide toughened alumina ceramics, thereby improving the impact toughness of the high chromium cast iron material, and then placing the casting in a heat treatment furnace, quenching by a graded cooling method after heating, and then performing three-stage tempering to obtain a processed part, which is beneficial to improving the toughness and impact resistance of the processed part, and is also beneficial to reducing the internal and external temperature difference and thermal stress during the cooling process of the processed part, and reducing the risk of cracking of the processed part, and then cleaning and preheating the surface of the processed part, and then using laser cladding to prepare a cladding layer on the surface of the pretreated processed part, and the cladding layer is made of titanium-plated cubic boron nitride powder, graphite, and nickel. The titanium-plated cubic boron nitride is made of cubic boron nitride, titanium trichloride and titanium hydride powder as raw materials, titanium trichloride and titanium hydride react under vacuum heating conditions to generate metallic titanium atoms, which are deposited on the surface of cubic boron nitride to form titanium carbide, thereby improving the hardness, impact toughness, high temperature resistance and other properties of the high chromium cast iron material. In addition, the titanium-plated cubic boron nitride has high hardness and graphite has good lubricity. The added titanium-plated cubic boron nitride powder and graphite can improve the wear resistance of the high chromium cast iron material in terms of wear resistance and friction reduction, and prepare a wear-resistant cladding layer with high hardness and low friction. In addition, the matrix structure is improved by heat treatment method, the matrix hardness is improved, the problem of interface cracking between high chromium cast iron and zirconia toughened alumina ceramics is avoided, and the mechanical properties of the high chromium cast iron material are improved. DETAILED DESCRIPTION

[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Example 1 A method for preparing a casting comprises the following steps: A1. Weigh the raw materials according to the mass percentage of each alloy element: C: 3.4%, Cr: 25%, Mn: 0.9%, Cu: 0.5%, Si≤1.00%, S≤0.06%, P≤0.06%, and the balance is Fe, place them in an induction furnace, heat and raise the temperature until all the raw materials are melted, remove impurities, and obtain molten iron; A2. Place the zirconia toughened alumina ceramic in a quartz boat, cover it with dry anhydrous ferrous chloride, and then place it at the bottom of a quartz tube. Pass argon as a protective gas, and use chemical vapor deposition to deposit an iron coating on the surface of the zirconia toughened alumina ceramic. The deposition temperature is 660°C, and the heating rate is 5°C / min. After the temperature rises to 660°C, hydrogen is passed in at a hydrogen flow rate of 205 mL / min. The temperature is kept for 1 hour to obtain an iron-deposited zirconia toughened alumina ceramic. A3. The iron-deposited zirconia toughened alumina ceramics are embedded in plastic foam, and cast using molten iron by lost foam casting at a temperature of 1680° C. to obtain a casting.

[0018] Example 2 A method for preparing titanium-coated cubic boron nitride comprises the following steps: Cubic boron nitride, titanium trichloride and titanium hydride powders are placed in a plating container at a mass ratio of 100:1.7:15, the plating temperature is set to 780°C, the vacuum degree is 0.01Pa, the temperature is kept at 0.01Pa for 15 minutes, the vacuum degree is maintained at 0.01Pa, and the furnace is cooled to room temperature to prepare titanium-coated cubic boron nitride.

[0019] Embodiment 3 A heat treatment process for a high wear-resistant high chromium cast iron material comprises the following steps: A. The casting prepared in Example 1 was placed in a heat treatment furnace, and the temperature in the furnace was first raised to 850°C, kept warm for 5 minutes, and then heated to 970°C at a heating rate of 30°C / min. After keeping warm for 20 minutes, it was first cooled to 940°C and kept warm for 30 minutes. After the end of the heat preservation, it was cooled to 710°C at a cooling rate of 10°C / s, and then cooled to 620°C at a cooling rate of 18°C / s, and then cooled to 500°C at a cooling rate of 11.5°C / s, kept warm for 40 minutes, and finally cooled to room temperature at a cooling rate of 280°C / min; B. Use a muffle furnace to temper the quenched casting. The first tempering temperature is 350°C, and the temperature is kept for 12 hours. The second tempering temperature is 300°C, and the temperature is kept for 15 hours. The third tempering temperature is 280°C, and the temperature is kept for 20 hours to obtain a processed part. C. Cut the workpiece into the required size by wire cutting, grind the surface with a grinder and sandpaper, clean it with alcohol and blow it dry, and preheat it at 285°C to obtain a pretreated workpiece; D. Take the titanium-plated cubic boron nitride powder, graphite and Ni60 self-fluxing powder prepared in Example 2 and mix them evenly in a mass ratio of 3.2:1:2.5, place them in a drying oven to dry and remove moisture, and pre-place them on the surface of the pretreated workpiece with a binder of sodium water glass. Then, under the protection of argon, use laser cladding to prepare a cladding layer with a laser power of 2.4 kW and a laser scanning speed of 250 mm / min to obtain a high-wear-resistant high-chromium cast iron material.

[0020] Embodiment 4 A heat treatment process for a high wear-resistant high-chromium cast iron material comprises the following steps: A. The casting prepared in Example 1 is placed in a heat treatment furnace, the temperature in the furnace is first raised to 875°C, and then heated to 1000°C at a heating rate of 32°C / min after being kept for 5 minutes. After being kept for 20 minutes, it is first cooled to 960°C and kept for 30 minutes. After the end of the heat preservation, it is cooled to 730°C at a cooling rate of 11.5°C / s, and then cooled to 650°C at a cooling rate of 20°C / s, and then cooled to 520°C at a cooling rate of 12°C / s, kept for 60 minutes, and finally cooled to room temperature at a cooling rate of 290°C / min; B. Use a muffle furnace to temper the quenched casting. The first tempering temperature is 400°C, and the temperature is kept for 12 hours. The second tempering temperature is 320°C, and the temperature is kept for 14 hours. The third tempering temperature is 300°C, and the temperature is kept for 20 hours to obtain a processed part. C. Cut the workpiece into the required size by wire cutting, grind the surface with a grinder and sandpaper, clean it with alcohol and blow it dry, and preheat it at 300°C to obtain a pretreated workpiece; D. Take the titanium-plated cubic boron nitride powder, graphite and Ni60 self-fluxing powder prepared in Example 2 and mix them evenly in a mass ratio of 5.2:1:3.5, place them in a drying oven to dry and remove moisture, and pre-place them on the surface of the pretreated workpiece with a binder of sodium water glass. Then, under the protection of argon, use laser cladding to prepare a cladding layer with a laser power of 2.4 kW and a laser scanning speed of 250 mm / min to obtain a high-wear-resistant high-chromium cast iron material.

[0021] Example 5 A heat treatment process for a high wear-resistant high-chromium cast iron material comprises the following steps: A. The casting prepared in Example 1 is placed in a heat treatment furnace, the temperature in the furnace is first raised to 900°C, kept warm for 10 minutes, then heated to 1100°C at a heating rate of 40°C / min, kept warm for 20 minutes, first cooled to 1070°C and kept warm for 30 minutes, after the end of the insulation, cooled to 840°C at a cooling rate of 12°C / s, then cooled to 750°C at a cooling rate of 20.5°C / s, then cooled to 560°C at a cooling rate of 13°C / s, kept warm for 30 minutes, and finally cooled to room temperature at a cooling rate of 302°C / min; B. Use a muffle furnace to temper the quenched casting, the first tempering temperature is 370°C, keep warm for 10 hours, the second tempering temperature is 305°C, keep warm for 14 hours, the third tempering temperature is 285°C, keep warm for 18 hours, and obtain the processed parts; C. Cut the workpiece into the required size by wire cutting, grind the surface with a grinder and sandpaper, clean it with alcohol and blow it dry, and preheat it at 285°C to obtain a pretreated workpiece; D. Take the titanium-plated cubic boron nitride powder, graphite and Ni60 self-fluxing powder prepared in Example 2 and mix them evenly in a mass ratio of 2.7:1:2.4, place them in a drying oven to dry and remove moisture, and pre-place them on the surface of the pretreated workpiece with a binder of sodium water glass. Then, under the protection of argon, use laser cladding to prepare a cladding layer with a laser power of 2.4 kW and a laser scanning speed of 250 mm / min to obtain a high-wear-resistant high-chromium cast iron material.

[0022] Comparative Example 1 A method for preparing a casting comprises the following steps: A1. Weigh the raw materials according to the mass percentage of each alloy element: C: 3.4%, Cr: 25%, Mn: 0.9%, Cu: 0.5%, Si≤1.00%, S≤0.06%, P≤0.06%, and the balance is Fe, place them in an induction furnace, heat and raise the temperature until all the raw materials are melted, remove impurities, and obtain molten iron; A2. Embed zirconia toughened alumina ceramics into plastic foam, adopt lost foam casting method, use molten iron for casting, set the temperature to 1680° C., and obtain a casting.

[0023] Comparative Example 2 A heat treatment process for a high wear-resistant high chromium cast iron material comprises the following steps: A. The casting prepared in Example 1 was placed in a heat treatment furnace, and the temperature in the furnace was first raised to 850°C, kept warm for 5 minutes, and then heated to 970°C at a heating rate of 30°C / min. After keeping warm for 20 minutes, it was first cooled to 940°C and kept warm for 30 minutes. After the end of the heat preservation, it was cooled to 710°C at a cooling rate of 10°C / s, and then cooled to 620°C at a cooling rate of 18°C / s, and then cooled to 500°C at a cooling rate of 11.5°C / s, kept warm for 40 minutes, and finally cooled to room temperature at a cooling rate of 280°C / min; B. Use a muffle furnace to temper the quenched casting at a tempering temperature of 350°C for 12 hours to obtain a processed part; C. Cut the workpiece into the required size by wire cutting, grind the surface with a grinder and sandpaper, clean it with alcohol and blow it dry, and preheat it at 285°C to obtain a pretreated workpiece; D. Take the titanium-plated cubic boron nitride powder, graphite and Ni60 self-fluxing powder prepared in Example 2 and mix them evenly in a mass ratio of 3.2:1:2.5, place them in a drying oven to dry and remove moisture, and pre-place them on the surface of the pretreated workpiece with a binder of sodium water glass. Then, under the protection of argon, use laser cladding to prepare a cladding layer with a laser power of 2.4 kW and a laser scanning speed of 250 mm / min to obtain a high-wear-resistant high-chromium cast iron material.

[0024] Comparative Example 3 A heat treatment process for a high wear-resistant high chromium cast iron material comprises the following steps: A. The casting prepared in Example 1 was placed in a heat treatment furnace, and the temperature in the furnace was first raised to 850°C, kept warm for 5 minutes, and then heated to 970°C at a heating rate of 30°C / min. After keeping warm for 20 minutes, it was first cooled to 940°C and kept warm for 30 minutes. After the end of the heat preservation, it was cooled to 710°C at a cooling rate of 10°C / s, and then cooled to 620°C at a cooling rate of 18°C / s, and then cooled to 500°C at a cooling rate of 11.5°C / s, kept warm for 40 minutes, and finally cooled to room temperature at a cooling rate of 280°C / min; B. Use a muffle furnace to temper the quenched casting. The first tempering temperature is 350°C, and the temperature is kept for 12 hours. The second tempering temperature is 300°C, and the temperature is kept for 15 hours to obtain the processed parts. C. Cut the workpiece into the required size by wire cutting, grind the surface with a grinder and sandpaper, clean it with alcohol and blow it dry, and preheat it at 285°C to obtain a pretreated workpiece; D. Take the titanium-plated cubic boron nitride powder, graphite and Ni60 self-fluxing powder prepared in Example 2 and mix them evenly in a mass ratio of 3.2:1:2.5, place them in a drying oven to dry and remove moisture, and pre-place them on the surface of the pretreated workpiece with a binder of sodium water glass. Then, under the protection of argon, use laser cladding to prepare a cladding layer with a laser power of 2.4 kW and a laser scanning speed of 250 mm / min to obtain a high-wear-resistant high-chromium cast iron material.

[0025] Comparative Example 4 A heat treatment process for a high wear-resistant high chromium cast iron material comprises the following steps: A. The casting prepared in Comparative Example 1 was placed in a heat treatment furnace, and the temperature in the furnace was first raised to 850°C, kept warm for 5 minutes, and then heated to 970°C at a heating rate of 30°C / min. After keeping warm for 20 minutes, it was first cooled to 940°C and kept warm for 30 minutes. After the end of the heat preservation, it was cooled to 710°C at a cooling rate of 10°C / s, and then cooled to 620°C at a cooling rate of 18°C / s, and then cooled to 500°C at a cooling rate of 11.5°C / s, kept warm for 40 minutes, and finally cooled to room temperature at a cooling rate of 280°C / min; B. Use a muffle furnace to temper the quenched casting. The first tempering temperature is 350°C, and the temperature is kept for 12 hours. The second tempering temperature is 300°C, and the temperature is kept for 15 hours. The third tempering temperature is 280°C, and the temperature is kept for 20 hours to obtain a processed part. C. Cut the workpiece into the required size by wire cutting, grind the surface with a grinder and sandpaper, clean it with alcohol and blow it dry, and preheat it at 285°C to obtain a pretreated workpiece; D. Take the titanium-plated cubic boron nitride powder, graphite and Ni60 self-fluxing powder prepared in Example 2 and mix them evenly in a mass ratio of 3.2:1:2.5, place them in a drying oven to dry and remove moisture, and pre-place them on the surface of the pretreated workpiece with a binder of sodium water glass. Then, under the protection of argon, use laser cladding to prepare a cladding layer with a laser power of 2.4 kW and a laser scanning speed of 250 mm / min to obtain a high-wear-resistant high-chromium cast iron material.

[0026] Comparative Example 5 A heat treatment process for a high wear-resistant high chromium cast iron material comprises the following steps: A. The casting prepared in Example 1 was placed in a heat treatment furnace, and the temperature in the furnace was first raised to 850°C, kept warm for 5 minutes, and then heated to 970°C at a heating rate of 30°C / min. After keeping warm for 20 minutes, it was first cooled to 940°C and kept warm for 30 minutes. After the end of the heat preservation, it was cooled to 710°C at a cooling rate of 10°C / s, and then cooled to 620°C at a cooling rate of 18°C / s, and then cooled to 500°C at a cooling rate of 11.5°C / s, kept warm for 40 minutes, and finally cooled to room temperature at a cooling rate of 280°C / min; B. Use a muffle furnace to temper the quenched casting. The first tempering temperature is 350°C, and the temperature is kept for 12 hours. The second tempering temperature is 300°C, and the temperature is kept for 15 hours. The third tempering temperature is 280°C, and the temperature is kept for 20 hours to obtain a processed part. C. Cut the workpiece into the required size by wire cutting, grind the surface with a grinder and sandpaper, clean it with alcohol and blow it dry, and preheat it at 285°C to obtain a pretreated workpiece; D. Take the titanium-plated cubic boron nitride powder prepared in Example 2 and the Ni60 self-fluxing powder and mix them evenly in a mass ratio of 3.2:2.5, place them in a drying oven to dry and remove moisture, and pre-place them on the surface of the pretreated workpiece with a binder of sodium water glass. Then, under the protection of argon, use laser cladding to prepare a cladding layer with a laser power of 2.4 kW and a laser scanning speed of 250 mm / min to obtain a high-wear-resistant high-chromium cast iron material.

[0027] Comparative Example 6 A heat treatment process for a high wear-resistant high chromium cast iron material comprises the following steps: A. The casting prepared in Example 1 was placed in a heat treatment furnace, and the temperature in the furnace was first raised to 850°C, kept warm for 5 minutes, and then heated to 970°C at a heating rate of 30°C / min. After keeping warm for 20 minutes, it was first cooled to 940°C and kept warm for 30 minutes. After the end of the heat preservation, it was cooled to 710°C at a cooling rate of 10°C / s, and then cooled to 620°C at a cooling rate of 18°C / s, and then cooled to 500°C at a cooling rate of 11.5°C / s, kept warm for 40 minutes, and finally cooled to room temperature at a cooling rate of 280°C / min; B. Use a muffle furnace to temper the quenched casting. The first tempering temperature is 350°C, and the temperature is kept for 12 hours. The second tempering temperature is 300°C, and the temperature is kept for 15 hours. The third tempering temperature is 280°C, and the temperature is kept for 20 hours to obtain a processed part. C. Cut the workpiece into the required size by wire cutting, grind the surface with a grinder and sandpaper, clean it with alcohol and blow it dry, and preheat it at 285°C to obtain a pretreated workpiece; D. Cubic boron nitride powder, graphite and Ni60 self-fluxing powder are mixed evenly in a mass ratio of 3.2:1:2.5, placed in a drying oven to dry to remove moisture and pre-placed on the surface of the pre-treated workpiece with a binder of sodium water glass. Then, under the protection of argon, a cladding layer is prepared by laser cladding with a laser power of 2.4 kW and a laser scanning speed of 250 mm / min to obtain a high-wear-resistant high-chromium cast iron material.

[0028] Performance Testing The high wear-resistant high chromium cast iron materials prepared in Examples 3-5 and Comparative Examples 2-6 were subjected to performance tests: the tensile strength and flexural strength of the materials were tested using a universal testing machine, the impact toughness and hardness of the samples were tested using a pendulum impact tester and a Rockwell hardness tester, each group of samples was tested 3 times, and the average value was taken; the wear resistance test was conducted using a multifunctional friction and wear testing machine, using a linear reciprocating wear method, using Si3N4 balls with a diameter of 4.7 mm, a load of 50 N, a time of 40 min, and a frequency of 2 Hz, and the data results are shown in Table 1.

[0029] Table 1 Test results of sample performance

[0030] It can be seen from the data in Table 1 that the high chromium cast iron materials prepared in Examples 3-5 of the present invention have excellent mechanical properties, high tensile strength, flexural strength, impact toughness and hardness, and small wear volume. Among them, only one-stage tempering was performed in Comparative Example 2, only two-stage tempering was performed in Comparative Example 3, the casting used in Comparative Example 4 was added with zirconium oxide toughened alumina ceramics, no graphite was added in Comparative Example 5, and untitanium-plated cubic boron nitride was added in Comparative Example 6. It was measured that the mechanical properties of the high chromium cast iron materials prepared in Comparative Examples 2-6 were reduced to varying degrees compared with Examples 3-5, and the wear resistance measured in Comparative Examples 5-6 was significantly reduced compared with Examples 3-5, indicating that the addition of graphite and titanium-plated cubic boron nitride can further improve the wear resistance of the high chromium cast iron material.

[0031] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0032] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A heat treatment process for high wear-resistant high chromium cast iron material, characterized in that: The following steps are involved: A. Place the casting in a heat treatment furnace, raise the temperature in the furnace to 850~900℃, keep it warm for 5~10min, then heat it to 970~1100℃ at a heating rate of 30~40℃ / min, keep it warm for 20~30min, then cool it to room temperature in stages; B. Use a muffle furnace to temper the quenched casting. The first tempering temperature is 350~400℃, and the temperature is kept for 10~12h. The second tempering temperature is 300~320℃, and the temperature is kept for 12~15h. The third tempering temperature is 280~300℃, and the temperature is kept for 17~20h to obtain the processed parts. C. Cut the workpiece into the required size by wire cutting, grind the surface with a grinder and sandpaper, clean it with alcohol and blow it dry, preheat it at 275-350℃, and obtain the pretreated workpiece; D. Mix titanium-coated cubic boron nitride powder, graphite and nickel-based alloy powder evenly, place them in a drying oven to dry them to remove moisture, and pre-place them on the surface of the pre-treated workpiece with a binder. Then, under the protection of argon gas, use laser cladding to prepare a cladding layer to obtain a high-wear-resistant high-chromium cast iron material.

2. The heat treatment process of high wear-resistant high chromium cast iron material according to claim 1, characterized in that: The specific steps of the graded cooling in step A are: first cooling to 940-1070°C and keeping warm for 20-30 minutes, cooling to 710-840°C at a cooling rate of 10-12°C / s after the insulation, cooling to 620-750°C at a cooling rate of 18-22°C / s, cooling to 500-560°C at a cooling rate of 11-13°C / s, keeping warm for 30-60 minutes, and finally cooling to room temperature at a cooling rate of 280-305°C / min.

3. The heat treatment process of high wear-resistant high chromium cast iron material according to claim 1, characterized in that: The method for preparing the casting in step A comprises the following steps: A1. Weigh the raw materials according to the mass percentage of each alloy element: C: 3.2~3.6%, Cr: 24~27%, Mn: 0.6~1.2%, Cu: 0.4~0.6%, Si≤1.00%, S≤0.06%, P≤0.06%, and the balance is Fe, place them in an induction furnace, heat and raise the temperature until all the raw materials are melted, remove impurities, and obtain molten iron; A2, taking zirconia toughened alumina ceramics and placing them in a quartz boat, covering them with dry anhydrous ferrous chloride, and then placing them at the bottom of a quartz tube, passing argon as a protective gas, and using chemical vapor deposition to deposit an iron coating on the surface of the zirconia toughened alumina ceramics to obtain iron-deposited zirconia toughened alumina ceramics; A3. The iron-deposited zirconia toughened alumina ceramics are embedded in plastic foam, and cast using molten iron by lost foam casting at a temperature of 1600-1780°C to obtain a casting.

4. The heat treatment process of the high wear-resistant high chromium cast iron material according to claim 3 is characterized in that: The chemical vapor deposition process conditions in step A2 are: deposition temperature 620-700° C., heating rate 3-6° C. / min, and hydrogen is introduced after the temperature rises to 620-700° C., with a hydrogen flow rate of 190-210 mL / min.

5. The heat treatment process of high wear-resistant high chromium cast iron material according to claim 1, characterized in that: The preparation method of titanium-coated cubic boron nitride in step D comprises the following steps: placing cubic boron nitride, titanium trichloride and titanium hydride powders into a plating container, setting the plating temperature to 760-795° C., the vacuum degree to 0.01-0.05 Pa, keeping the temperature for 10-20 minutes, maintaining the vacuum degree to 0.01-0.05 Pa, and cooling to room temperature with the furnace to prepare titanium-coated cubic boron nitride.

6. The heat treatment process of high wear-resistant high chromium cast iron material according to claim 5, characterized in that: The mass ratio of the cubic boron nitride, titanium trichloride and titanium hydride powder is 97-105:1.5-3:14.5-17.

7. The heat treatment process of high wear-resistant high chromium cast iron material according to claim 1, characterized in that: In the step D, the mass ratio of the titanium-plated cubic boron nitride powder, graphite and nickel-based alloy powder is 2.7-5.5:1:2.4-3.

5.

8. The heat treatment process of high wear-resistant high chromium cast iron material according to claim 1, characterized in that: The nickel-based alloy powder in step D is Ni60 self-fluxing powder, and the mass fractions of the chemical components are 15.5% Cr, 3.5% B, 4.0% Si, 0.8% C, 15.0% Fe, 3.0% W, and the rest is Ni; the binder is sodium water glass.

9. The heat treatment process of high wear-resistant high chromium cast iron material according to claim 1, characterized in that: The laser cladding process conditions in step D are: laser power 2.2-2.5 kW, laser scanning speed 240-260 mm / min.

10. A high wear-resistant high chromium cast iron material, characterized in that: The product is obtained by the heat treatment process described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing high-chromium wear-resistant alloy through laser cladding

    CN103233224A

  • Iron-based ceramic particle reinforced composite materials preparation method

    CN108097931A

  • Titanized cubic boron nitride clad sheet and preparation process thereof

    CN108950561A

  • Modified ceramic particle reinforced iron-based composite material and preparation method thereof

    CN111804907A

  • Preparation method of ceramic particle inlayed-cast reinforced metal-based wear-resistant composite board

    CN113714488A

Cited By

  • Vacuum pump surface melting plating process

    CN120366774A